(untitled) (REMUNOM, 2026)
This research aimed to evaluate the effect of a reduced-FODMAP diet as an adjuvant nutritional treatment in Inflammatory Bowel Diseases (IBD), aiming to reduce classic gastrointestinal symptoms. A thorough search was conducted in the following databases: PubMed (Medline), Virtual Health Library (BVS), and Scientific Electronic Library Online (SciELO). Inclusion criteria were scientific articles (observational and clinical trials) in Portuguese and English, published between 2019 and 2024, addressing the effect of FODMAPs in the nutritional therapy of IBD, available in full text, and involving humans. Exclusion criteria were articles outside the time period, editorials, review articles, case reports, experience reports, and duplicate articles. Low-FODMAP diets may improve intestinal symptoms and quality of life in patients undergoing treatment for inflammatory bowel diseases. However, more studies are needed to understand how FODMAPs work in relation to inflammatory bowel diseases.